Analysis Aplication of Cherry Leaves Booking Inreduce Blood Glucose Levels in Diabetes Mellitus Patients - Novi Afrianti (PT.Mantaya Idea Batara, 2023)
Diabetes Mellitus is a non-communicable disease which is the 4th leading cause of death in the world. This disease is characterized by an increase in blood glucose accompanied by impaired metabolism of carbohydrates, fats, and proteins as a result of insufficient insulin function. When the body does not use insulin, the function of the pancreas decreases and there is no secretion of hormones for metabolic processes, so the body gets tired faster. Therefore, treatment is needed, one of which is nonpharmacological therapy that has a hypoglycemic effect, namely cherry leaves. Cherry leaf is an alternative medicine for diabetes mellitus which is used by boiling cherry leaves using water. The purpose of this paper is to describe the analysis of administration of decoction of cherry leaves in reducing blood glucose levels in patients with diabetes mellitus based on empirical studies over the last ten years. The design of this writing is a literature review searched through the google scholar database, using the PICO (problem, intervention, comparation, outcome) framework so that four journals are obtained according to the research topic. The results of the literature review can be concluded that there is an effect of giving decoction of cherry leaves in reducing blood glucose levels in patients with diabetes mellitus.